Screening and Supplementation for Iron Deficiency and Iron Deficiency Anemia During Pregnancy: Updated Evidence Report and Systematic Review for the US Preventive Services Task Force - Cantor, Amy G; Holmes, Rebecca; Bougatsos, Christina; Atchison, Chandler; DeLoughery, Thomas; Chou, Roger (JAMA : the journal of the American Medical Association, 2024)
In 2015 the US Preventive Services Task Force (USPSTF) found insufficient evidence to assess the balance of benefits and harms of routine screening and supplementation for iron deficiency anemia during pregnancy. To update the 2015 review on screening for iron deficiency anemia, in addition to iron deficiency during pregnancy, to inform the USPSTF. Ovid MEDLINE and Cochrane databases through May 24, 2023; surveillance through May 24, 2024. Randomized clinical trials of iron supplementation, screening effectiveness, treatment, and harms; observational studies of screening. Dual review of abstracts, full-text articles, study quality, and data abstraction. Data were pooled using a random-effects model. Maternal and infant clinical outcomes, hematologic indices, and harms. Seventeen trials (N = 24 023) on maternal iron supplementation were included. Iron supplementation was associated with decreased risk of maternal iron deficiency anemia at term (4 trials, n = 2230; 8.6% vs 19.8%; relative risk, 0.40 [95% CI, 0.26-0.61]; I2 = 20.5%) and maternal iron deficiency at term (6 trials, n = 2361; 46% vs 70%; relative risk, 0.47 [95% CI, 0.33-0.67]; I2 = 81.9%) compared with placebo or no iron supplement. There were no statistically significant differences in maternal quality of life, rates of gestational diabetes, maternal hemorrhage, hypertensive disorders of pregnancy, cesarean delivery, preterm birth, infant low birth weight, or infants small for gestational age for maternal iron supplementation compared with placebo or no supplementation. Harms of iron supplementation included transient gastrointestinal adverse effects. No studies evaluated the benefits or harms of screening for iron deficiency or iron deficiency anemia during pregnancy. Data on the association between iron status and health outcomes, such as hypertensive disorders of pregnancy and preterm birth, were very limited. Routine prenatal iron supplementation reduces the incidence of iron deficiency and iron deficiency anemia during pregnancy, but evidence on health outcomes is limited or indicates no benefit. No studies addressed screening for iron deficiency or iron deficiency anemia during pregnancy. Research is needed to understand the association between changes in maternal iron status measures and health outcomes.